Analisis Keefektifan Iklan Sebagai Strategi Komunikasi Pemasaran Produk Jenang CV. Mubarookfood Cipta Delicia Menggunakan EPIC Model - Rizka Octaviani; Sapja Anantanyu; Hanifa Ihsaniyati (Universitas Sebelas Maret, 2018)
The purpose of this research is to determine the effectiveness of advertising CV. Mubarokfood could be seen from four dimensions EPIC (Empathy, Persuasion, Impact and Communication) and to determine the dimensions of EPIC which most dominan. The data used are primary data and secondary data. The technique of collecting data using questionnaires, interviews, and recording. The basic method is Descriptive-Analytic. Analysis using the EPIC model. A questionnaire was distributed to 100 respondents in the area of Central Stores CV. Mubarookfood and Kudus city. Interviews were conducted with the marketing manager. The results showed that the ads that are presented in the form of print media (Brochure), outdoor media (X- Banner, Billboard, Neonbox, Banner) and electronic media (Radio, Internet). The results of the analysis of the effectiveness of ads based EPIC model shows that the advertising of the CV. Mubarokfood seen from the dimensions empathy obtained an average score of 4.596, the dimensions of persuasion have a score of 4.244, the dimensions of impact have a score of 4.605 and dimensions of communication have a score of 4.471. The third dimension is included in the scale of